Energetic supplementation for maintenance or development of Apis mellifera L. colonies - Gabriela Pinto de Oliveira; Samir Moura Kadri; Bruno Giovane Emilio Benaglia; Paulo Eduardo Martins Ribolla; Ricardo de Oliveira Orsi (Journal of Venomous Animals and Toxins including Tropical Diseases)
Abstract Background: The nutritional requirements of honeybees (Apis mellifera) for their complete development need to be supplied through food sources available in the environment, since honeybees are insects that depend directly on blossoming food sources. However, at certain times a food-supply reduction can promote nutritional stress, thus necessitating food supplementation for maintenance or production stimulus of the colonies. Thus, the determination of optimal energy supplementation can assist in the maintenance and production of colonies. Methods: Twenty Apis mellifera beehives were used (with five beehives per treatment): CTL, control (without feeding); SJ, sugarcane juice; SS, sugar syrup; and IS, inverted sucrose. We evaluated the food consumption, population development, and physiological state (expression of vitellogenin and hexamerin 70a genes) of each colony. Results: The results showed that the supplementation of colonies with sugar syrup resulted in an intermediate consumption level (894.6 ± 291 mL) and better development (384.9 ± 237.3 and 158.3 ± 171.6 cm2, sealed and open brood, respectively). Furthermore, this diet ensured that the colonies were in a good physiological state, as bees fed this diet presented the highest relative expression levels of vitellogenin and hexamerin 70a among all the diets tested. Conclusions: Therefore, sugar syrup is concluded to be the best artificial energetic food for use in the supplementation of honeybee colonies.